ANALISIS PEMAHAMAN PETANI PADI TENTANG ZAKAT PERTANIAN DAN IMPLEMENTASINYA DI DESA SUNGAI ABANG KABUPATEN SAROLANGUN - Yosi Silviana; Addiarrahman Addiarrahman; Efni Anita (Jurnal Publikasi Manajemen Informatika, 2023)
Zakat is one of the pillars of Islam, zakat is issuing a certain portion of certain assets up to the nisab to those who are entitled to receive it and is an obligation for Muslims that has been determined by the Qur'an, the Sunnah of the Prophet and the consensus of the scholars. Sungai Abang Village is a village that has quite extensive rice fields, so some people earn from agricultural products, but some of the farmers do not understand about agricultural zakat so they are still lacking in practicing agricultural zakat. This study aims to determine how farmers understand about agricultural zakat and its implementation. This study uses a qualitative approach, the data in this study were obtained from primary data and secondary data. Using the method of observation, interviews and documentation. Analysis of the data obtained from interviews, field notes, and other materials, arranged systematically so that they are easy to understand and describe in the form of quotations to find out how farmers understand about agricultural zakat and its implementation in Sungai Abang Village, Sarolangun Regency. The results show that farmers' understanding of agricultural zakat is still lacking, some of them do not know what agricultural zakat is, their understanding of agricultural zakat is still limited, they equate alms with zakat. The implementation of agricultural zakat in Sungai Abang Village, Sarolangun Regency, farmers still use traditional methods which have become a hereditary habit.